Looking beyond collaboration: socioemotional positive, negative and task-oriented behaviors in Human-Robot Group Interactions - Oliveira, R.; Arriaga, P.; Correia, F.; Paiva, A. (International Journal of Social Robotics, 2020)
In this paper, we aim to increase the understanding of human-robot interaction by considering the goal orientation displayed by the robot (i.e., competitive vs. cooperative) and the role displayed by each player (partner vs. opponent) in an entertainment group scenario. Sixty participants engaged in a card game called Sueca (two robots and two humans). Each participant played with each of the other players, and the goal orientation was manipulated by the set of verbal utterances displayed by the robot. Using a coding scheme based on Bales Interaction Process Analysis, the video-recorded interactions were analysed in terms of socioemotional positive, negative and task-oriented behaviours. A marginal multilevel modelling analysis yielded signifi cant interactions between the robotic addressee and the role the robot displayed in the socioemotional and task-oriented behaviours. Overall, our main results demonstrated the following: (1) Participants directed more behaviours towards partners than opponents, although most of these behaviours occurred between humans when they were partners. (2) When comparing players in the role of opponents, participants directed more socioemotional behaviours towards robots than towards the other human player. (3) No difference in task-oriented behaviours was observed among any of the players in this condition. These results suggest the occurrence of different behavioural patterns in competitive and collaborative interactions with robots that might be useful to inform the future development of more socially effective robots.